National medical service
1943-10-20 1943 1940s 15 pages -9- from the selected members of voluntary Management Boards. The hospital is financed by the rates and much depends on the progressive state of the community seeing that no minimum institutional standard is set by the Ministry of Health in working permissive legislation. Many of the Local Authority hospitals have improved greatly in every way since the Local Government Act of 1929, and in the best institutions the equipment and standard are higher than in nany [many] voluntary hospitals even the Teaching Schools. Many buildings are more recent and so modern. The medical profession through its representative organisations are fearful of the control if a full time State Medical Service materialises, of the type of Local Authority members in many districts. They are asking for medical administration by larger regional councils. Unfortunately Whitley Council Machinery has never yet been a feature of British Hospital administration and yet its possibilities for harmonious interchange of views are enormous. The medical profession in order to secure procrastination on pending changes are even asking for Local Government reform, and great improvement of social services and surroundings, before any inauguration of changes in medical services. The Local Authority institutions are compelled by law to admit cases needing admission and have no right of differential choice. Consequently they receive an undue proportion of chronic cases, less interesting from the unusual or scientific point of view and needing less emergency handling and services such as surgical operative procedure. There is less drama and showmanship but none the less efficient treatment. Again here, the conditions vary a great deal, depending on institutional size, part of country, interest of electors etc. Clinics The majority of clinics are administered by Local Authorities for purposes of Ante Natal Maternity Work, Infant Welfare, Venereal Diseases, Tuberculosis Examinations etc. They perform invaluable medical work, both ameliorative and preventative, which are seldom undertaken by the voluntary institutions. Many of these duties are statutory and connected with these clinics are institutional beds sometimes in Maternity Homes (L.A.) or Sanatoria. All these institutions are well administered. There are many private profit-making Sanatoria for tuberculosis and other patients but only exceptionally are they associated with voluntary hospitals. There are a very few private clinics run by doctors for special complaints, such as rheumatism. Convalescent Homes are attached to institutions of both types but the attachment to the voluntary hospitals is much looser. More convalescent homes are badly needed. Private nursing homes, though allowed at present should only be permitted under strict regulation and so too should most treatment centres for massage etc. In Local Authority hospitals there is no question of private paying wards. In both types of hospitals the Almoner system exists by which through trained lay social officers investigations are made into patients' means or ability to make contribution and payments towards treatments in order to secure finance to cover as much as possible the cost of treatment. This system should be abolished. Admittance to hospital or clinic should be on the merit of the individual case, need for appropriate treatment and free to all. Its effect on an embarrassed patient may be to increase his mental reaction to anxiety and apprehension. (B) Medical Services These are mainly of two types (a) Preventive and (b) Curative or Ameliorative. 292/847/2/113